Common errors in problem solving in Arithmetic committed by Grade Four pupils in the Division of Southern Leyte - Dayata, Alfredo H. 1914- (s.n.], 1967)
This study determined and analyzed the common errors in problem solving committed by Grade Four pupils in the Division of Southern Leyte.